Marketing Mix Affecting Parents’ Decision Making on Choosing Private Schools in Prachuap Khiri Khan Province - Thammachart, Rattapon; Tuvadaratragool, Sumeth (Suan Dusit Graduate School Academic Journal, 2023)
The objectives of this research were 1) to study the level of parents’ decision making on choosing private schools in Prachuap Khiri Khan province, 2) to study the level of marketing mix of private schools in Prachuap Khiri Khan province, and 3) to study the causal relationship between marketing mix and parents’ decision making on choosing private schools in Prachuap Khiri Khan province. This research was quantitative research. The research sample was parents of students studying private schools in Prachuap Khiri Khan province and the sample size was 390 parents. Questionnaire was used as a data collection tool, which had IOC index equal to 1 in each question and reliability of 0.952. This research used purposive sampling technique. Statistics used included mean, standard deviation, and multiple regression. The results revealed that 1) the overall parents’ decision making on choosing private schools in Prachuap Khiri Khan province was at the high level. When considering an individual component, problem recognition came first, followed by information search, choosing decision, evaluation of alternative, and post-choosing behavior, respectively, 2) the overall marketing mix of private schools in Prachuap Khiri Khan province was at the high level. When considering an individual component, people come first, followed by process, physical evidence, product, price, promotion and place, respectively and 3) marketing mix including product, place, people, process, and physical evidence related to parents’ decision making on choosing private schools in Prachuap Khiri Khan province at the statistical significance level of 0.05. Whereas price and promotion did not relate to parents’ decision making on choosing private schools in Prachuap Khiri Khan province.